Dependence of Dandelion ( Wigg.) Seed Reproduction Indices on Intensity of Motor Traffic Pollution - Elena A. Erofeeva (SAGE Publishing, 2014)
Dandelion ( Taraxacum officinale Wigg.) seed reproduction indices such as the total number of seeds, the number of normally developed seeds and underdeveloped seeds per anthodium, and seed weight are suggested to assess the level of environmental pollution (bioindication). However, the non-monotonic dose-response dependences (hormesis and paradoxical effects) of these indices are insufficiently explored upon exposure to pollution. We studied the dependence of some T. officinale seed reproduction indices on intensity of motor traffic pollution in wide range of values over 2 years of observation. In 2010, the increase in traffic intensity induced a monotonic increase in the total seed number and the number of normally developed seeds. Besides, motor traffic pollution decreased the number of undeveloped seeds and seed weight in comparison with the control. In 2011, for all studied T. officinale indices except seed weight, complicated non-monotonic dependences on traffic intensity were found that could be attributed to paradoxical effects. It is hypothesised that the significant differences in the studied dependencies in 2010-2011 were caused by changes in weather conditions because traffic intensity did not differ significantly between the two observation years.